Model updating in structural dynamics — Uncertainties on the position and orientation of sensors and actuators. (13th October 2015) - Batou, A.
Abstract: This research concerns the updating of computational models in presence of uncertainties related to the position and the orientation of the sensors and actuators. Such uncertainties yield uncertainties in the correspondence between the experimental dynamical responses and the dynamical responses calculated using the computational model. These uncertainties in the response increase with frequency and have to be taken into account when updating the parameters of the computational model in order to obtain a robust estimation of these parameters. This paper provides a complete methodology to take into account and analyse such uncertainties. Furthermore, an optimal sensor placement method is proposed so that (1) the measured data are as sensitive as possible with respect to updating parameters and (2) the measured data are as robust as possible with respect to position/orientation uncertainties. The methodologies developed here are illustrated through two numerical applications.